2020
DOI: 10.3390/educsci10110333
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Agile Methodologies in an Engineering Course

Abstract: At present, a new generation of students is studying at universities with their specific abilities and skills. In addition to hard skills, potential employers also require significantly developed soft skills from their employees. The school, and not just the university, is entering this process in a different position than in the past due to the changing requirements placed on it. Activities in the school environment must adapt to emerging trends. This article explains how present-day requirements on graduates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Snowball unstructured interviews reinforced the outcomes of the quantitative analysis of the survey data and the qualitative evaluation of open-ended responses. The objective was to inform engineering educators about the need to focus on non-technical skills within the curriculum [1,27] and help to prioritize which soft skills are reported as most important for entry-level engineering roles.…”
Section: Purpose and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Snowball unstructured interviews reinforced the outcomes of the quantitative analysis of the survey data and the qualitative evaluation of open-ended responses. The objective was to inform engineering educators about the need to focus on non-technical skills within the curriculum [1,27] and help to prioritize which soft skills are reported as most important for entry-level engineering roles.…”
Section: Purpose and Problem Statementmentioning
confidence: 99%
“…There is no universally accepted classification of what constitutes a soft skill [17,18]. Researchers use terms such as non-cognitive, non-technical skills; people skills; transferable skills; employability skills; and interpersonal skills to refer to soft skills [17,18,27]. Most research equates soft skills with people skills or the ability to get along with or work effectively with others [4].…”
Section: What Are Soft Skills?mentioning
confidence: 99%
“…Moreover, the reason for getting such results is partly due to the problem associated with the packing of the shreds using the closed molding as this problem was not faced using the open mold productions [49]. Practically, the impact is negatively significant, but at the same time, the time spent, the preparation procedure, and the energy consumed are much less than the autoclave process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, local waste of CFRP has been increasing recently due to booming growth in using carbon fiber; therefore, part of the commitment toward the society from the university was to increase the awareness through the students by engaging with research projects trying find with solutions to reduce the negative impact. A complete program was designed for the students to be trained on handling the waste in order to proceed with the planned activities, since gaining hands-on skills is an essential matter for the students to acquire knowledge in order to cope with the diverse demands of working life [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…AM fosters knowledge in the skills and enhances technical and nontechnical skills. [ 5 11 ] According to the 14 th annual state Agile Global Survey report, 58% of the respondents practiced the scrum framework, and 85% reported that daily meetings help in higher productivity, followed by a retrospective meeting, sprint planning, and review meetings. Only 4% of respondents used AM in health care, pharmaceutical companies, and educational institutions.…”
Section: Introductionmentioning
confidence: 99%